IgG3 enhances neutralization potency and Fc effector function of an HIV V2-specific broadly neutralizing antibody. - Simone I Richardson; Bronwen E Lambson; Andrew R Crowley; Arman Bashirova; Cathrine Scheepers; Nigel Garrett; Salim Abdool Karim; Nonhlanhla N Mkhize; Mary Carrington; Margaret E Ackerman; Penny L Moore; Lynn Morris (PLoS Pathogens)
Broadly neutralizing antibodies (bNAbs) protect against HIV infection in non-human primates and their efficacy may be enhanced through interaction with Fc receptors on immune cells. Antibody isotype is a modulator of this binding with the IgG3 subclass mediating potent Fc effector function and is associated with HIV vaccine efficacy and HIV control. BNAb functions are typically assessed independently of the constant region with which they are naturally expressed. To examine the role of natural isotype in the context of a bNAb lineage we studied CAP256, an HIV-infected individual that mounted a potent V2-specific bNAb response. CAP256 expressed persistently high levels of plasma IgG3 which we found mediated both broad neutralizing activity and potent Fc function. Sequencing of germline DNA and the constant regions of V2-directed bNAbs from this donor revealed the expression of a novel IGHG3 allele as well as IGHG3*17, an allele that produces IgG3 antibodies with increased plasma half-life. Both allelic variants were used to generate CAP256-VRC26.25 and CAP256-VRC26.29 IgG3 bNAbs and these were compared to IgG1 versions. IgG3 variants were shown to have significantly higher phagocytosis and trogocytosis compared to IgG1 versions, which corresponded to increased affinity for FcγRIIa. Neutralization potency was also significantly higher for IgG3 bNAbs, particularly against viruses lacking the N160 glycan. By exchanging hinge regions between subclass variants, we showed that hinge length modulated both neutralization potency and Fc function. This study showed that co-operation between the variable and natural IgG3 constant regions enhanced the polyfunctionality of antibodies, indicating the value of leveraging genetic variation which could be exploited for passive immunity.